Love In Feuerbach Philosophy - Shbani, Monzer; Shaaban , Razan (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Feuerbach tried to make the power of love a kind of power that cannot be matched with any other power as love defeats all his opponents even if God is one of them. Love is always victorious. That's what made the concept of love in Feuerbach’s ideas a distinguished and unprecedented concept comparing to all concepts handled by those philosophers before him. This kind of love dominates the body and soul together and it is inseparable from our body, may not live outside our soul, it is the basis of the body and the essence of the spirit. Feuerbach wanted to make love a link between a mankind and another so there is no love if one existence and the other is absent. Feuerbach doesn’t limit himself at this point but goes on to ignore the existence of human being without being in love or loved by other person. That who does not love does not exist, even religion has neither benefit nor importance if it is not based on love because love is the reason and core in other words love is the reason behind the existence of religion.